2013
DOI: 10.1089/apc.2012.0312
|View full text |Cite
|
Sign up to set email alerts
|

All Black People Are Not Alike: Differences in HIV Testing Patterns, Knowledge, and Experience of Stigma Between U.S.-Born and Non–U.S.-Born Blacks in Massachusetts

Abstract: Non-U.S.-born black individuals comprise a significant proportion of the new diagnoses of HIV in the United States. Concurrent diagnosis (obtaining an AIDS diagnosis in close proximity to an initial diagnosis of HIV) is common in this subpopulation. Although efforts have been undertaken to increase HIV testing among African Americans, little is known about testing patterns among non-U.S.-born black people. A cross-sectional survey was self-administered by 1060 black individuals in Massachusetts (57% non-U.S.-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…13,15,23,29 Some have attributed this to ''anticipated stigma,'' which can be measured using a different scale, and is designed to assess the extent to which individuals anticipate negative intra-and interpersonal consequences should they contract HIV/STIs in the future, and operates independently of personal endorsement of stigmatizing beliefs or stereotypes. 30,31 Although our research did not investigate anticipated stigma or potential delays in seeking care, we did see a large percentage of youth not seeing doctors regularly (34%). However in this area of San Francisco, where outreach services are numerous, a large proportion of men had been tested for STI and HIV, although approximately 18% of those tested had been tested in jail or juvenile hall; in California, all youth are STI tested at entry to correctional unit facilities.…”
Section: Discussionmentioning
confidence: 87%
“…13,15,23,29 Some have attributed this to ''anticipated stigma,'' which can be measured using a different scale, and is designed to assess the extent to which individuals anticipate negative intra-and interpersonal consequences should they contract HIV/STIs in the future, and operates independently of personal endorsement of stigmatizing beliefs or stereotypes. 30,31 Although our research did not investigate anticipated stigma or potential delays in seeking care, we did see a large percentage of youth not seeing doctors regularly (34%). However in this area of San Francisco, where outreach services are numerous, a large proportion of men had been tested for STI and HIV, although approximately 18% of those tested had been tested in jail or juvenile hall; in California, all youth are STI tested at entry to correctional unit facilities.…”
Section: Discussionmentioning
confidence: 87%
“…41,42,[53][54][55][56][57][58][59] Having an undocumented immigration status was associated with not ever being tested for HIV in a study in South Flordia. 52 Reasons identified in other studies for foreign birth being associated with delayed diagnosis include stigma, 56,60,61 language barriers, 58,61 and less knowledge about HIV. 56,61 Late HIV/AIDS diagnosis in urban areas was associated with heterosexual compared with MSM and IDU modes of HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Research on migrants in Australia, the US, Canada and Europe highlight migrants' vulnerability to HIV, with rates exceeding those of the general host population [7][8][9][10][11][12]. A striking example of this comes from Belgium where, between 2002 and 2006, figures showed that, despite accounting for \1 per cent of the population, migrants from Sub-Saharan Africa accounted for nearly half (45.7 per cent) of newly diagnosed cases of HIV [11].…”
Section: Introductionmentioning
confidence: 99%